Identification of Enteric Bacteria in Houseflies (Musca domestica) found in Selected Public Eateries in Davao City - Junelle P. Silguera; Alden S. Basay; Mecaila Alenna M. Villareal (Future Science / FSH-PH Publications, 2026)
Houseflies (Musca domestica) are recognized mechanical vectors of various enteric pathogens, particularly in areas with poor sanitation. Their feeding and breeding habits on waste materials make them effective carriers of disease-causing microorganisms. Previous studies have linked houseflies to the transmission of infections such as shigellosis, cholera, and typhoid fever. This study aimed to identify enteric bacteria carried by houseflies collected from selected public eateries in Davao City and assess their potential role in bacterial transmission. A total of 27 samples were examined using conventional microbiological techniques, including microscopy and biochemical testing. Bacteria from the genera Escherichia, Klebsiella, Enterobacter, and Citrobacter were identified. Statistical analysis using the chi-square test revealed no significant variation in bacterial presence across different collection sites. The findings suggest that houseflies consistently harbor enteric bacteria regardless of location, emphasizing their role as potential vectors in public food environments. This study therefore recommends that local health authorities implement strict preventive measures in waste management, regular inspection, and sanitation permits to reduce the risks of foodborne pathogen transmission.